Associations of Plasma BDNF and BDNF Gene Polymorphism with Cardiometabolic Parameters in Thai Children: A Pilot Study - Kanjana Suriyaprom; Banchamaphon Pheungruang; Somchai Pooudong; Pumpath Putpadungwipon; Chutima Sirikulchayanonta (Journal of Nutrition and Metabolism)
Background. Childhood obesity is an important public health crisis worldwide. The brain-derived neurotrophic factor (BDNF) has been demonstrated to play a role in controlling energy homeostasis and cardiovascular regulation. Objectives. To examine brain-derived neurotrophic factor (BDNF) levels and anthropometric-cardiometabolic and hematological parameters in obese and nonobese children and to determine whether two BDNF gene polymorphisms (G196A and C270T) are linked to BDNF levels, obesity, and anthropometric-cardiometabolic and hematological parameters among Thai children. Methods. This case-control study included an analysis of 469 Thai children: 279 healthy nonobese and 190 obese children. Anthropometric-cardiometabolic and hematological variables and BDNF levels were measured. Genotyping of BDNF G196A and C270T was performed using the polymerase chain reaction-restriction fragment length polymorphism technique. Results. Children in the obese group had significantly higher white blood cell counts and some cardiometabolic parameters. Although the difference in BDNF level between the nonobese and obese groups was not significant, BDNF level was significantly positively correlated with hematological and cardiometabolic parameters, including blood pressure, triglycerides, and triglycerides and the glucose index. The BDNF G196A polymorphism in children was only associated with decreased systolic blood pressure p<0.05, while the BDNF C270T polymorphism was found not to be related to BDNF levels, obesity, or other parameters after adjusting for potential covariates. Conclusions. These findings in Thai children suggest that obesity is associated with increased cardiometabolic risk factors, but not with BDNF levels or the two BDNF polymorphisms studied, while the BDNF G196A polymorphism is a beneficial marker for controlling blood pressure among Thai children.